Examining the Effectiveness of Athlete Celebrity Endorser Characteristics and Product Brand Type: The Endorser Sexpertise Continuum - Christina S. Simmers; Datha Damron-Martinez; Diana L. Haytko (Journal of Applied Sports Management, 2009)
This research furthers the theoretical perspectives that athlete endorsers are brands unto themselves, and that athlete-endorser effectiveness is determined by congruent pairings of the athlete-endorser brand and the product brand by introducing the Endorser Sexpertise Continuum. This model categorizes athlete celebrity endorsers on the Endorser Sexpertise Continuum with anchor points referred to as “acquirable expertise” and “likeability.” As in successful brand alliances, this model suggests the types of products/brands the athlete celebrities would be most successful in endorsing, depending on their positioning on the continuum.
Keywords: Sport marketing; brand management; celebrity endorser; sponsorship; product endorsement; celebrity athlete; athlete spokesperson; source credibility; source attractiveness